Penalaran Proporsional Siswa Kelas Menengah dalam Menyelesaikan Masalah Matematika Ditinjau dari Adversity Quotient : Proportional Reasoning of Middle School Students in Solving Mathematical Problems Viewed From Adversity Quotient - Khumairoh, Binta; Amin, Siti Maghfirotun; Wijayanti, Pradnyo (Pedagogia : Jurnal Pendidikan, 2020)
This study aims to describe students’ proportional reasoning profile of junior high school students in mathematical problem solving based on Adversity Quotient (AQ) type climbers, campers, and quitters. This qualitative research was conducted to 22 female students who were in eight grade that used documentation, test, and interview to gather the data. Analyzing the students’ test result and then interviewing them for each category were done for the analysis process. The result show that there are 9.1% climber students, 72.7% camper students, and 18.2% quitter students. The result of this study showed that there were differencies about proportional reasoning activities based on type Adversity Quotient (AQ) climbers, campers, and quitters.